Dalcetrapib reduces risk of new-onset diabetes in patients with coronary heart disease - Schwartz, GG; Leiter, LA; Ballantyne, CM; Preiss, D; Et al. (American Diabetes Association, 2020)
Objective Incident type 2 diabetes is common among patients with recent acute coronary syndrome and is associated with an adverse prognosis. Some data suggest that cholesteryl ester transfer protein (CETP) inhibitors reduce incident type 2 diabetes. We compared the effect of treatment with the CETP inhibitor dalcetrapib or placebo on incident diabetes in patients with recent acute coronary syndrome. Research design and methods In the dal-OUTCOMES trial, 15,871 patients were randomly assigned to treatment with dalcetrapib, 600 mg daily, or placebo, beginning 4–12 weeks after an acute coronary syndrome. Absence of diabetes at baseline was based on medical history, no use of antihyperglycemic medication, and hemoglobin A1c and serum glucose levels below diagnostic thresholds. Among these patients, incident diabetes after randomization was defined by any diabetes-related adverse event, new use of antihyperglycemic medication, hemoglobin A1c ≥6.5%, serum glucose ≥7.0 mmol/L (fasting) or ≥11.1 mmol/L (random). Results At baseline, 10,645 patients (67% of the trial cohort) did not have diabetes. During a median follow-up of 30 months, incident diabetes was identified in 403 of 5,326 patients (7.6%) assigned to dalcetrapib and in 516 of 5,319 (9.7%) assigned to placebo, corresponding to absolute risk reduction of 2.1%, hazard ratio of 0.77 (95% CI 0.68–0.88; P < 0.001), and a need to treat 40 patients for 3 years to prevent 1 incident case of diabetes. Considering only those with prediabetes at baseline, the number needed to treat for 3 years to prevent 1 incident case of diabetes was 25. Dalcetrapib also decreased the number of patients who progressed from normoglycemia to prediabetes and increased the number who regressed from diabetes to no diabetes. Conclusions In patients with a recent acute coronary syndrome, incident diabetes is common, and is reduced substantially by treatment with dalcetrapib.